Effects of a new magnesium-rich artificial cerebrospinal fluid on contractile 5-hydroxytryptamine and endothelin receptors in rat cerebral arteries. (2nd November 2019) - Cheng, Ya-Wen; Guo, Yi-Chen; Li, Guo-Liang; Deng, Yong-Ning; Li, Wen-Juan; Xu, Gao-Feng; Deng, Zhong; Cao, Yong-Xiao; Luo, Guo-Gang
ABSTRACT: Objectives Cerebral vasospasm after subarachnoid haemorrhage (SAH) is associated with cerebrovascular contractile receptor upregulation resulted from haemolysis in the subarachnoid space. This study developed a new magnesium-rich artificial cerebrospinal fluid (MACSF) formula and investigated its effects on receptor-mediated contraction in rat basilar arteries. Methods Clear and haemorrhagic cerebrospinal fluid (CSF) were collected from patients with hydrocephalus or SAH. MACSF was freshly prepared using clinical intravenous injections. Rat basilar arteries were segmented and incubated with clear CSF, haemorrhagic CSF or MACSF. The contractile responses were studied by myograph. The messenger ribonucleic acid (mRNA) and protein expression of 5-hydroxytryptamine 1B (5-HT1B ), endothelin subtype B (ETB ) and endothelin subtype A (ETA ) receptors were evaluated by real-time polymerase chain reaction (PCR) and Western blot analyses. Results Haemorrhagic CSF exposure shifted the contractile curves induced by 5-hydroxytryptamine (5-HT), sarafotoxins 6c (S6c) and endothelin-1 (ET-1) leftward with increased maximal contraction values. Furthermore, mRNA and protein expression were markedly elevated for 5-HT1B, ETB and ETA receptors on arteries exposed to haemorrhagic CSF. However, the contractile responses to 5-HT, S6c or ET-1 and expression of 5-HT1B, ETB and ETA receptors in rat cerebral arteries exposed to MACSF remained unaffected compared to those exposed to clear CSF. Besides, unlike normal saline which can inactive in-vitro vessels, MACSF can maintain their physiological activity. Conclusion Haemorrhagic CSF induces upregulation of 5-HT1B, ETB and ETA receptors in rat cerebral arteries. However, MACSF can maintain in-vitro rat basilar arteries in good physiological activity and normal expression of contractile 5-HT and ET receptors.